Family Members’ Perspectives on the Unmet Care Needs of People Living With Dementia in Nursing Homes - Paananen, Jenny; Moore, Vanessa; Blomqvist, Katarina; Kulmala, Jenni; Pirhonen, Jari (United States, 2025)
While the number of older people living with dementia grows, savings in public resources leads to situations where services and supports for older people are cut, even in the traditionally generous Nordic welfare states, such as Finland. This development is expected to lead to care poverty, meaning older people are not receiving the services they need. Our aim was to uncover whether care poverty already exists within institutional care for older adults in Finland. Thematic analysis was utilized to study 19 interviews with family members of people with dementia living in a nursing home. Signs of care poverty were found in relation to timeliness and safety of access to long-term care and quality of professional care. In addition, the threshold of questioning the care system was high, and managing disagreements about care with professionals was challenging for the family members. The results raise concerns that reducing long-term care risks the whole concept of welfare states. Family members should be more systematically involved in needs assessment and decision-making concerning the care of older people with dementia.